Thinking chemistry. - Lewis, Michael; Waller, Guy. (New York : Bangkok : Oxford university press, 1986)
Thinking Chemistry covers material in a unique and highly visual way. At every stage the student is encouraged to think and understand, rather than simply memorize the facts.
includes index.
Keywords: Chemistry